Persistence of high plasma glucose, insulin and cortisol concentrations in elderly patients with proximal femoral fractures. - Frayn, K; Stoner, H; Barton, R; Heath, D; Galasko, C (1983)
Plasma glucose, insulin and cortisol concentrations were measured in elderly patients with femoral neck fractures. The results have been compared with those in younger injured patients as well as younger and elderly control subjects. There was a prolonged elevation of plasma glucose, insulin and cortisol concentrations after femoral neck fractures, in contrast to a rapid return to normal in younger injured patients. Comparison with the control groups suggested that this might reflect the effects of immobility rather than of age or of injury per se. The pattern of insulin resistance together with a high cortisol concentration could hinder recovery.